Effectiveness of University Leaders' Behavior and the Faculty Members' Motivation towards the Work in the Iraqi Colleges of Nursing - Jassim, Basima; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2015)
Objective(s): The present study aims at identifying the Iraqi Colleges of Nursing Deans' leadershipbehaviors effectiveness and faculty members' motivation towards work in these colleges.Methodology: Descriptive design has been used for the sample survey manner, which is theappropriate approach to the study of social phenomena in the field where provides data on the reality ofthese phenomena and relations between the causes and consequences and an analysis of it and perhapsthe factors affecting it and how it appears. The study relies on a questionnaire to collect data from theparticipants which is composed of (86) items distributed on three axes: First, the demographiccharacteristics which are composed of (8) items, second, (40) items to measure motivation towardswork and the third (38) items to measure the effectiveness of the leadership behavior of the Deans ofthe Colleges of Nursing. Content validity of the questionnaire is determined through panel of expertswho are asked to present their opinion about the content of the questionnaire. The stability has beenachieved through the use of reliability coefficients to determine the internal consistency of thequestionnaire. Data of the study are collected through field visits to the Iraqi Nursing Colleges andpersonal interviews with respondents. The study population includes all Iraqi Colleges of Nursing atthe time of the study which are distributed through thirteen Governorates. The sample of the studyincludes (66) subjects who are (55) faculty member and (11) Dean. The sample is purposive "nonprobability"and selected based on the selection criteria to select professor and assistant professor. Thestudy data are analyzed through the descriptive data analysis approach (Frequencies and percentages)and inferential data analysis approach (Chi-square test and Cronbach Alpha Correlation coefficient).The results: The study findings indicate that variables of age groups and years of work have impactupon the improvement of faculty members' motivation towards work in the Iraqi Colleges of Nursing.Variables of Deans' age, gender, education, years of work as dean and training have no influence on theleadership behavior of the Colleges of Nursing Deans.Recommendations: The study recommends that we have to promote democratic style practiced byleaders and present freedom and independence of the faculty member because of the stature in thecommunity. The study suggests that there should be an interest for leadership behavior with facultymembers, so they can be aware of the desired approaches toward achieving the objectives of theuniversity. The preparation of a proposed program to increase the activation of the performance offaculty in Iraqi Colleges of Nursing and carrying out other studies concerned with this subject and thework of preparing a proposal for the creation of democratic leader in the Iraqi Colleges of Nursing.